UFIDA (B) - Chen, E.; McFarlan, F. Warren (Franklin Warren); Yang, Bin ([London] : SAGE, 2016)
This case highlights the leadership, cultural and organizational structure dimensions of UFIDA. The case begins with Founder/Chairman Wang Wenjing's rags-to-riches story. Then UFIDA's senior and middle management of different backgrounds talk about their leader, Chairman Wang Wenjing. They voice their opinions on Wang Wenjing's leadership style, UFIDA's corporate culture and vision.
Originally Published in: Chen, E., McFarlan, F.W., Yang, B. (2011). UFIDA (B). 0-310-112. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; UFIDA (Firm); Corporate culture -- Case studies; Leadership -- Case studies; Computer software industry -- Management -- Case studies